Post-Synthetic and In Situ Vacancy Repairing of Iron Hexacyanoferrate Toward Highly Stable Cathodes for Sodium-Ion Batteries - Wan, Min; Zeng, Rui; Meng, Jingtao; Cheng, Zexiao; Chen, Weilun; Peng, Jiayu; Zhang, Wuxing; Huang, Yunhui (Nano-Micro Letters, 2021)
Iron hexacyanoferrate (FeHCF) is a promising cathode material for sodium-ion batteries. However, FeHCF always suffers from a poor cycling stability, which is closely related to the abundant vacancy defects in its framework. Herein, post-synthetic and in-situ vacancy repairing strategies are proposed for the synthesis of high-quality FeHCF in a highly concentrated Na4Fe(CN)6 solution. Both the post-synthetic and in-situ vacancy repaired FeHCF products (FeHCF-P and FeHCF-I) show the significant decrease in the number of vacancy defects and the reinforced structure, which can suppress the side reactions and activate the capacity from low-spin Fe in FeHCF. In particular, FeHCF-P delivers a reversible discharge capacity of 131 mAh g−1 at 1 C and remains 109 mAh g−1 after 500 cycles, with a capacity retention of 83%. FeHCF-I can deliver a high discharge capacity of 158.5 mAh g−1 at 1 C. Even at 10 C, the FeHCF-I electrode still maintains a discharge specific capacity of 103 mAh g−1 and retains 75% after 800 cycles. This work provides a new vacancy repairing strategy for the solution synthesis of high-quality FeHCF. Highlights: 1 Post-synthetic and in-situ vacancy repairing strategies effectively decrease the defects in FeHCF. 2 Vacancy reduction improves the structure and cycling stability of FeHCF. 3 Vacancy reduction boosts the capacity contribution from low-spin Fe in FeHCF.